PENINGKATAN HASIL BELAJAR IPA MELALUI MODEL PROBLEM BASED LEARNING (PBL) DENGAN MEDIA BENDA KONKRETPADA SISWA KELAS V SD - Afifah, Dina; Minsih, Minsih (Trapsila: Jurnal Pendidikan Dasar, 2021)
This Classroom Action Research aims to improve Class V science learning outcomes through the PBL (Problem Based Learning) model with concrete object media at SD Negeri Kemiri 2 in 2020/2021, totaling 33 students. Methods of data collection are carried out through interviews, observation, tests and documentation. The results showed an increase in science learning outcomes with an increase in learning outcomes after the action. In practice, researchers conducted research using two cycles of action. In practice, this classroom action research is carried out repeatedly by following predetermined cycle stages so that goals are achieved. In the first cycle the increase in the class average increased from 67.18 in the pre-cycle to 71.36 after being given action in cycle 1. Students who reached the KKM in the pre-cycle 51.51% increased to 71.50% of the students reached the KKM so there was an increase 99%. In the second cycle the class average increased from 71.36 to 81.14. with 80.29% of students reaching KKM so that there was an increase of 8.79%. The conclusion of this study is that the PBL (Problem Based Learning) model with the media of concrete objects can improve the learning outcomes of grade V science learning at SD Negeri Kemiri 2.